Códigos Produto Multiníveis para Correção de Erros Bi-Separáveis com Aplicações em CriptografiaDOI: 10.14209/jcis.1995.1 - M. C. de Souza, R.; C. de Souza, J. (Journal of Communication and Information Systems, 2015)
This paper describes a new private-key cryptosystem based on multilevel product codes, which are single random-error-correcting and have the capacity for correcting bi-separable errors of arbitrary weight. The encryption process makes use of an error structure that is not found in any real communication channel and that leads to a superior performance in comparison with similar schemes. Aspects of the encoding and decoding operations are discussed and the capacity of the cryptosystem to resist the attacks that are typically used against encryption schemes based on error control codes is analysed.